2022
DOI: 10.21203/rs.3.rs-1183911/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cooperative binding of TCR and CD4 to pMHC enhances TCR sensitivity

Abstract: Antigen recognition of CD4+ T cells by the T cell receptor (TCR) can be greatly enhanced by the coreceptor CD4. Yet, understanding of the molecular mechanism is hindered by the ultra-low affinity of CD4 binding to class-II peptide-major histocompatibility complexes (pMHC). Using two-dimensional (2D) mechanical-based assays, we determined a CD4–pMHC interaction to have 3-4 logs lower affinity than cognate TCR–pMHC interactions, and to be susceptible to increased dissociation by forces (slip bond). In contrast, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…We introduced the catch-bond intensity I as a dimensionless scaled metric for the bond lifetime vs force curve and generated four model parameters that describe the curve’s geometric features. Upon analyzing all catch-slip and slip-only bond profiles (a total of 48 curves) published to date by four independent laboratories 46,8,13,15,32,38,39 , we found that these quantities do a better job to predict TCR function than any other quantities. This finding explains how force amplifies TCR signaling and antigen discrimination, because I is defined by a force curve and n * and θ only predict signaling when they assume none-zero values at F > 0.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…We introduced the catch-bond intensity I as a dimensionless scaled metric for the bond lifetime vs force curve and generated four model parameters that describe the curve’s geometric features. Upon analyzing all catch-slip and slip-only bond profiles (a total of 48 curves) published to date by four independent laboratories 46,8,13,15,32,38,39 , we found that these quantities do a better job to predict TCR function than any other quantities. This finding explains how force amplifies TCR signaling and antigen discrimination, because I is defined by a force curve and n * and θ only predict signaling when they assume none-zero values at F > 0.…”
Section: Discussionmentioning
confidence: 97%
“…Another boundary condition to be considered by future studies is that imposed by the coreceptor CD4 and CD8, as the co-ligation of the coreceptor prolongs bond lifetimes, amplifies catch bonds, and may even changes slip-only bonds to catch-slip bonds 7,13,39 . Future studies should also consider how to extend the current models to pre-TCR catch and slip bonds with a broad range of ligands 37,41 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations